2020
DOI: 10.1080/09168451.2019.1662278
|View full text |Cite
|
Sign up to set email alerts
|

Daily administration of Sake Lees (Sake Kasu) reduced psychophysical stress-induced hyperalgesia and Fos responses in the lumbar spinal dorsal horn evoked by noxious stimulation to the hindpaw in the rats

Abstract: We tested whether Sake Lees (SL) had inhibitory effects on hyperalgesia in the hindpaw under psychophysical stress conditions. Male rats were subjected to repeated forced swim stress treatments (FST) from Day −3 to Day −1. Intraperiotoneal administration of SL which contained low concentration of ethanol (SLX) was conducted after each FST. On Day 0, formalin-evoked licking behaviors and Fos responses in the lumbar spinal cord (DH) and several areas within the rostral ventromedial medulla (RVM) were quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…Currently, interpretation of immobility behaviors as depression-like behaviors is controversial [ 179 , 180 ]; however, FS is the useful model for studying the basis for stress-induced hyperalgesia, since FS (10–20 min/day) could consistently increase nociceptive responses in the animals. For example, FS for 2–3 days causes hyperalgesia in the hindpaw, increased neural activities in the lumbar dorsal horn [ 181 , 182 ] and in the supra-spinal areas [ 183 , 184 ].…”
Section: Preclinical Models For Psychological Stress and Deep Craniofacial Pain ( Table 1 )mentioning
confidence: 99%
“…Currently, interpretation of immobility behaviors as depression-like behaviors is controversial [ 179 , 180 ]; however, FS is the useful model for studying the basis for stress-induced hyperalgesia, since FS (10–20 min/day) could consistently increase nociceptive responses in the animals. For example, FS for 2–3 days causes hyperalgesia in the hindpaw, increased neural activities in the lumbar dorsal horn [ 181 , 182 ] and in the supra-spinal areas [ 183 , 184 ].…”
Section: Preclinical Models For Psychological Stress and Deep Craniofacial Pain ( Table 1 )mentioning
confidence: 99%
“…Saccharomyces cerevisiae generates carboxypeptidases, proteinases, and aminopeptidases (Van Den Hazel et al, 1996). Sake lees and their constituents have been reported to improve hepatic lipid accumulation (Kubo et al, 2017), reduce blood pressure (Saito et al, 1994), mitigate hyperalgesia (Shimizu et al, 2020), prevent allergic rhinitis-like symptoms (Kawamoto et al, 2011), and suppress acute alcohol-induced liver injury (Izu et al, 2006). Several studies reported reductions in the viable counts of aerobic bacteria in raw ham treated with Sake lees (Matsuoka et al, 2006) and altered texture in squid meat cured with Sake lees based on sensory tests, texturometry, and protein decomposition analyses (Shimomura et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A brainstem pain-modulating system, also known as descending pain controls, with its output node in the rostral ventromedial medulla, regulates deep craniofacial nociception through the regulation of neural activities in the C1/C2 regions [44]; changes in neural activities in the rostral ventromedial medulla could facilitate nociception in various psychological stress models [45][46][47]. The rostral ventromedial medulla, including nucleus raphe magnus and LPGi, has descending 5-HT fibers to the C1/C2 region [13,48].…”
Section: Discussionmentioning
confidence: 99%